DESKRIPSI TINGKAH LAKU TANGKASI ( Tarsius Spectrum ) SAAT MEMASUKI DI LUBANG SARANG POHON DI CAGAR ALAM TANGKOKO - Urulamo, Jemi; Kiroh, H. J.; Hendrik, Manopo; Buyung, J. R. (ZOOTEC, 2014)
ABSTRACT DESCRIPTION OF TANGKASI BEHAVIOR (Tarsius Spectrum) WHEN ENTERING THEÂ Â  HOLE NEST TREE IN TANGKOKO NATURE RESERVE. Tarsier in Tangkoko Nature Reserve Batuangus many inhabit cavities in trees or root piles. Tarsier nest is a place that is safe from predators. This study aims to obtain data regarding some behavior that appears when Tarsier Tarsius activity around the nest tree at Tangkoko Nature Reserve. To determine the percentage of respective behavior that tarsiers in the show in the morning, afternoon and evening. The variables measured were some behaviors that arise between them. Grooming behavior, resting behavior, seeking shelter behavior, play behavior, data were analyzed and presented in a descriptive, which describes and explains the general description of the results of direct observations, the results showed that more Tangkasi doing grooming on morning with a percentage of 37.15%. during the day with a percentage of 31.19% early evening with a percentage of 31.19%. Tangkasi resting behavior is most prevalent during the day ie 38.70%. At night with a percentage of 32.25%, in the afternoon with 29.03% percentage. Sheltering behavior more activity in the morning with a percentage of 38.07% and the time of day with the percentage of 33.02%. While in the afternoon with a percentage of 28.89% behavior played almost evenly in each time. On the morning after finished foraging Tangkasi playing with percentage of 30, 18%, and the percentage of time during the day with 32.88% and a maximum in the late afternoon with a percentage of 37.38%. Keywords: Behavior Tangkasi (Tarsius spectrum)